«Queriendo poner mi ánima en carrera de salvación»: la muerte en Granada (siglos XVII XVIII ) - autor, Sin (Cuadernos de Historia Moderna, 2002)
This article looks at a range of approximately 1.000 testaments from seventeenth and eighteenth-century Granada, which throw light on the context of death and burial at the time as a ritual of community. The study suggests two great changes over the early modem period, in line with developments in other parts of Europe: firstly, a ‘spiritualization’ of death as a result of the Counter Reformation, with a greater emphasis on prayers for the dead, and secondly a certain ‘individualism’ or ‘privacy’ of death, corresponding perhaps o both religious and family changes in the age of the Enlightenment.